Hubungan antara Pola Pemberian Makanan Pendamping ASI dengan Status Gizi pada Bayi usia 6-12 bulan - Saudah, Noer; Anggun Purbasari, Rike (Jurnal Keperawatan Bina Sehat, 2011)
The pattern of giving side food of mother’s milk that is not suitable could bring some effect against nutrient status of baby. This phenomena is happened in Polindes Tanjangrono village of Tanjangrono whereas still many mothers give side food of mother’s in wrong way and its could have effect to the nutrient status of baby 6 – 12 month old. The purpose of this research is to know correlation between pattern of giving side food of mother’s milk and nutrients status of baby 6 – 12 month old. This research use analytic correlation design with cross sectional. Independent variable in this research is pattern of giving side food of mother’s milk, dependent variable is nutrient status of baby 6-12 month old. Population of this research are all of mothers who have baby 6-12 month old in Polindes Tanjungrono Village of Tanjangrono District of Ngoro Regency of Mojokerto in July 2011. Sample is taken by consecutive sampling counted of 40 respondents. Data analyzed by Spearman rho tes with the result r = 0.001 dan α = 0.05. so r < α, its mean H0rejected and H1accepted, so there are correlation between pattern in giving side food of mother’s milk and nutrient status of baby 6-12 month old in Polindes Tanjungrono Village of Tanjangrono District of Ngoro Regency of Mojokerto in July 2011. The result of this research show that the more appropriate pattern of giving side food of mother’s milk better nutrient status of baby 6-12 month old. Its hoped that respondents more improve their knowledge about pattern of giving side food of mother’s milk in the right way so nutrient status of baby will be better.Keyword :The Pattern on Side Food of Mother’s milk, Nutrient Status